2005
DOI: 10.1021/la051954b
|View full text |Cite
|
Sign up to set email alerts
|

Combination of Electrografting and Atom-Transfer Radical Polymerization for Making the Stainless Steel Surface Antibacterial and Protein Antiadhesive

Abstract: A two-step "grafting from" method has been successfully carried out, which is based on the electrografting of polyacrylate chains containing an initiator for the atom transfer radical polymerization (ATRP) of 2-(tert-butylamino)ethyl methacrylate (TBAEMA) or copolymerization of TBAEMA with either monomethyl ether of poly(ethylene oxide) methacrylate (PEOMA) or acrylic acid (AA) or styrene. The chemisorption of this type of polymer brushes onto stainless steel surfaces has potential in orthopaedic surgery. Thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
104
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 108 publications
(108 citation statements)
references
References 30 publications
2
104
2
Order By: Relevance
“…Although the competing mechanisms remain unclear, a large body of data suggests that both physical and chemical modifications of a material surface can be engineered to limit bacterial colonization. [5][6][7][8][9][10]12,13,20,22 For example, as shown in Figure 1, coating surgical-grade titanium alloy with a synthetic PEM of PAA and PAH reduced colony density of waterborne S. epidermidis bacteria by orders of magnitude after immersion in 10 7 bacteria/mL. Reduced colonization over both 2 and 4 h incubation timescales is relevant to medical procedure durations involving, for example, cardiac assist and orthopedic implant devices.…”
Section: Bacterial Colonization Can Be Reduced By Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the competing mechanisms remain unclear, a large body of data suggests that both physical and chemical modifications of a material surface can be engineered to limit bacterial colonization. [5][6][7][8][9][10]12,13,20,22 For example, as shown in Figure 1, coating surgical-grade titanium alloy with a synthetic PEM of PAA and PAH reduced colony density of waterborne S. epidermidis bacteria by orders of magnitude after immersion in 10 7 bacteria/mL. Reduced colonization over both 2 and 4 h incubation timescales is relevant to medical procedure durations involving, for example, cardiac assist and orthopedic implant devices.…”
Section: Bacterial Colonization Can Be Reduced By Materialsmentioning
confidence: 99%
“…7,[13][14][15] Because biofilm formation requires the initial, stable attachment of a viable bacteria population on a surface, 4 another promising approach to limiting microbial colonization is prevention of bacterial adhesion to material substrata prior to colonization. Others have reported that poly(ethylene glycol)-conjugated polypeptides confer adhesion resistance and suggested that such results may be due to high degrees of substrata surface hydration; 16 this speculation was not systematically tested.…”
Section: Introductionmentioning
confidence: 99%
“…Ignatova et al 13 Identical letters denote no significant differences among groups. Different letters denote significant differences among groups vity against S. aureus and S. mutans biofilms, but was inactive against the C. albicans biofilm.…”
Section: Discussionmentioning
confidence: 99%
“…8,11,12 In a previous report, PTBAEMA was successfully incorporated into polyethylene or stainless steel surfaces. 11,13 In addition, the polymer has also exhibited highly antimicrobial properties against Escherichia coli and S. aureus 11,13 and S. mutans in denture base resin. Marra et al 7 also observed antimicrobial properties against S. mutans and S. aureus when incorporating PTBAEMA in denture base resin, with no activity against C. albicans.…”
Section: Introductionmentioning
confidence: 99%
“…Discarded PLA can also be degraded fast [9] and is thus deemed as a good environmentally protective plastic. In addition, poly[2-(tert-butylaminoethyl)methacrylate](TBMA) is a newly invented antimicrobial polymer [10] that is hydrophobic. TBMA is produced via an atom-transfer radical-polymerization (ATRP) [11,12].…”
Section: Introductionmentioning
confidence: 99%